Towards A Systemic Methodology For Evaluating The Impact Of Interventions On Organizational Effectiveness - Kilmann, Ralph H.; Herden, Richard P. (Academy of Management Review, 1976)
A methodology is proposed by which relevant persons can systematically partake in conceptualizing which components of effectiveness are most central to an organization, how to choose evaluation methodologies to measure these components, and how to evaluate the impact of a change program to enhance the effectiveness of the organization.